Design and Innovative Application of Ship CCUS Technology Under the Requirements of Green Shipping - Niyu Zhang; Xinpeng Wang; Cong Wang; Zhongxiu Peng; Youxiao Chen; Lianhao Liu; Lijie Chen; Jiawei Hu; Wei Wei; Xuesong Li (Journal of Marine Science and Engineering, 2025)
In the context of green shipping, carbon capture, utilization, and storage (CCUS) technology is widely recognized as an effective approach for maritime emission reduction. However, existing onboard CO2 capture systems (OCCS) face challenges including high retrofit complexity, operational limitations, significant deadweight tonnage loss, and compromising feasibility. This study addresses these issues through modular redesign and standardization of two core components: the capture device and CO2 storage system. We developed clustered storage units to ensure secure CO2 storage while maximizing economic efficiency, with optimal deployment determined through parameter optimization. The work further examines post-capture processing methods and implementation barriers for onboard CCUS, establishing practical pathways to advance decarbonization technologies and mature maritime CCUS industry chains.